English English - Kadek Ayu Dwipayanti; Ni Made Ratminingsih; Made Hery Santosa; Kadek Ayu Dwipayanti; Ni Made Ratminingsih; Made Hery Santosa (Jurnal Riset Madrasah Ibtidaiyah (JURMIA), 2026)
The success of literacy and student learning achievements is supported by the ability to understand reading as an important learning skill. However, for some students in Indonesia, difficulties in relating new material to prior knowledge, as well as a lack of vocabulary, make this a problem. Therefore, this study aims to explore the use of storytelling as a teaching strategy to improve students' reading comprehension and to explore more deeply the perceptions of fourth-grade students regarding its use in the classroom. Using a qualitative descriptive method, seven fourth-grade students from SD Negeri 3 Banjar Jawa, Singaraja, Bali, participated in the study. Data collection was conducted through semi-structured interviews and analyzed using thematic analysis. There were six main themes from the research results, which showed that the use of storytelling as a learning strategy could make learning more interesting, encourage active student participation, and enable students to understand the material through the content of the story easily. As a result, the use of storytelling is an effective strategy to be applied in learning.